“Systems trauma”: A qualitative study of work-related distress among service providers to people experiencing homelessness in Canada - Nick Kerman; John Ecker; Emmy Tiderington; Amanda Aykanian; Vicky Stergiopoulos; Sean A. Kidd (SSM - Mental Health, 2022)
Service provision to people experiencing homelessness is challenging and stressful work. Yet, there is a dearth of evidence on how the work experiences of service providers contribute to mental health distress and wellness. This qualitative study examined the contributing factors to workplace mental health among service providers to people experiencing homelessness in Canada, with the aim of establishing a causal theory for how work-related challenges cause distress. In-depth interviews were conducted with 40 service providers working in the homeless service, supportive housing, and harm reduction sectors across Canada. Data were analyzed using a grounded theory-informed approach. The workplace mental health of service providers was centred on the concept of “systems trauma,” which refers to the structural and systemic factors that exacerbate the difficulty of service providers’ work, putting them at-risk of work-related mental health distress. “Systems trauma” had multifaceted causes and consequences, as did the organizational- and individual-level factors that protected service providers against its impacts. Overall, the findings highlight how the same sociopolitical context that negatively affects people experiencing homelessness also shapes the workplace mental health of service providers. Supports for managing moral distress, policy and public initiatives to improve the valuation of work with people experiencing homelessness, dedicated funding for workforce development, and further investment in primary and secondary prevention of homelessness are recommended to promote workplace mental health.